Case-based reasoning in product design competitive analysis - Leong, Chong Yen. (2012)
The new product development (NPD) process is recognized as the major factor for gaining competitive advantage in many industries. The Quality deployment function (QFD) process is one of the methods applied to drive the design conceptualization process based on customer needs and technical requirements. Competitive assessment is also performed in QFD to aid engineers to identify significant functionalities of competitors’ products to the consumers. However, the inadequate knowledge on products information available in the market discourages firms to perform exhaustive comparisons of new product conceptual designs against competitors’ products. Product benchmarking for competitive advantage cannot be performed in the early stages of NPD process. Hence, the case based reasoning (CBR) strategy is introduced for the competitive analysis of conceptual designs. The guiding principles of CBR are applied to the design conceptualization phase of product development process to integrate product competitive benchmarking in concepts evaluations. New product competitive improvements are to be made in early stages of NPD to minimize the cost of design changes. The entire product development process is revised and restructured to accommodate the application of CBR strategy. To achieve a competitor-driven, customer-oriented and self-sufficient CBR system, the usage of competitive assessment results from QFD and external cases consists of competitors’ products information are introduced. A CBR framework is developed using myCBR software program to demonstrate the establishment of case base, case retrieval, adaptation, revision and retention processes. The product domain of camera product designs is selected for the application of this CBR framework for competitive analysis. Cases of camera products are acquired, organized, defined and similarity functions are modelled in the CBR framework. The implementation of this CBR framework demonstrated the challenges in CBR system design, limitations for product competitive analysis and impact of competitive analysis via CBR strategy to a firm’s product strategy and project management in NPD.